The role of sex and autonomy-connectedness in internalizing and externalizing personality pathology, coping and axis-I pathology: among psychiatric and healthy elderly. (3rd June 2017) - Bachrach, Nathan; Croon, Marcel; Bekker, Marrie
ABSTRACT: Objectives: In the current study we investigated the relationship of sex and autonomy-connectedness with internalizing and externalizing personality disorder symptoms (PDS), coping and axis-I pathology in older age. Method: A path model was tested which was based on neo-analytical object relation, attachment- and primary-personality theory, among 100 clinical and 106 non-clinical elderly. Results: In line with our model, autonomy-connectedness (self-awareness and capacity of managing new situations) was strongly associated to internalizing PDS in both groups. In both groups, neither sex nor autonomy-connectedness predicted externalizing PDS. Sex, internalizing as well as externalizing PDS and reactive defensive coping were associated to axis-I psychopathology. Conclusions: We conclude that sex and autonomy-connectedness were, similarly as in adult populations, associated to internalizing PDS and axis-I pathology. Treatment of elderly with internalizing PDS and axis-I psychopathology should therefore focus on enhancing autonomy-connectedness.